SOCIETAL COSTS ASSOCIATED WITH NEOVASCULAR AGE-RELATED MACULAR DEGENERATION IN THE UNITED STATES. Issue 2 (February 2016) - Brown, Melissa M.; Brown, Gary C.; Lieske, Heidi B.; Tran, Irwin; Turpcu, Adam; Colman, Shoshana
Abstract : Purpose: The purpose of this study was to use a cross-sectional prevalence-based health care economic survey to ascertain the annual, incremental, societal ophthalmic costs associated with neovascular age-related macular degeneration. Methods: Consecutive patients (n = 200) with neovascular age-related macular degeneration were studied. A Control Cohort included patients with good (20/20–20/25) vision, while Study Cohort vision levels included Subcohort 1: 20/30 to 20/50, Subcohort 2: 20/60 to 20/100, Subcohort 3: 20/200 to 20/400, and Subcohort 4: 20/800 to no light perception. An interviewer-administered, standardized, written survey assessed 1) direct ophthalmic medical, 2) direct nonophthalmic medical, 3) direct nonmedical, and 4) indirect medical costs accrued due solely to neovascular age-related macular degeneration. Results: The mean annual societal cost for the Control Cohort was 6, 116 and for the Study Cohort averaged 39, 910 ( P < 0.001). Study Subcohort 1 costs averaged 20, 339, while Subcohort 4 costs averaged 82, 984. Direct ophthalmic medical costs comprised 17.9% of Study Cohort societal ophthalmic costs, versus 74.1% of Control Cohort societal ophthalmic costs ( P < 0.001) and 10.4% of 20/800 to no light perception subcohort costs. Direct nonmedical costs, primarily caregiver, comprised 67.1% of Study Cohort societal ophthalmic costs, versus 21.3% (1, 302/6, 116) of Control Cohort costs ( P < 0.001) and 74.1% of 20/800 to no light perception subcohort costs. Conclusion: Total societal ophthalmic costs associated with neovascular age-related macular degeneration dramatically increase as vision in the better-seeing eye decreases. Abstract : The societal costs associated with neovascular age-related macular degeneration correlate most highly with vision in the better-seeing eye and range from 6, 116 annually with 20/20 to 20/25 vision to 82, 984 with 20/800 to no light perception vision.